The reality of the application of the comprehensive quality standards in the care of the orphan child field study at the orphanage in Lattakia - dallal, Mirna; Soufi, Zeina (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The current study aims to highlight the need to implement the concepts of comprehensive quality in the orphan care and to monitor the strengths and weaknesses in the practices of the orphanage from the perspective of comprehensive quality. To achieve the objectives of the study, the scholar adopted the descriptive analytical method using the questionnaire as a research tool, which was applied to a sample of all members of the original community of supervisors of the orphanage in Latakia (25 unites). The study concluded that the orphanage achieved an acceptable level of care, with some disadvantages. First, the failure of orphanage administration to employ the results of evaluating the performance of the staff in the formulation of plans; second, the absence of a specialized teaching staff and experts in vocational education to supervise the teaching of children; and finally, lack of partnership between parents and employers to train children in different professions.